1985
DOI: 10.1002/pssa.2210910219
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Implantation into Silicon. Infra-Red Absorption Spectra and Electrical Properties

Abstract: Hydrogen and deuterium implantations into crystalline silicon (c‐Si) are carried out at room temperature. Infra‐red spectra and electrical property studies are performed on these samples before and following annealing. Analysis of the vibrational spectra shows at least two types of bonding for hydrogen in c‐Si, which are identified as SiH1, (SiH2)2 units. A strong evidence of SiH2 group formation is obtained for the relatively low hydrogen concentration in c‐Si in comparison with a‐Si:H. On the basis of the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 21 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…1) strong long-wavelength absorption due to the free conduction band electrons that is reversibly changed by quenching at 70 to 210 C. The free-carrier IR absorption decreases considerably at 80 K while a reversibly changed broad feature at about 600 cm ± ±1 , related to the electron excitations from the E t % E c ± ± 0.06 eV shallow donor level to the conduction band, appears in the spectra. The E t value evaluated from the long-wavelength absorption edge at %500 cm ± ±1 is close to the H-donor level value determined by Hall measurements [2]. In the spectra there are also relatively weak bands at 400, 440, and 465 cm ± ±1 as well as the 375 cm ± ±1 local band, all strongly correlated with the 600 cm ± ±1 broad band.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…1) strong long-wavelength absorption due to the free conduction band electrons that is reversibly changed by quenching at 70 to 210 C. The free-carrier IR absorption decreases considerably at 80 K while a reversibly changed broad feature at about 600 cm ± ±1 , related to the electron excitations from the E t % E c ± ± 0.06 eV shallow donor level to the conduction band, appears in the spectra. The E t value evaluated from the long-wavelength absorption edge at %500 cm ± ±1 is close to the H-donor level value determined by Hall measurements [2]. In the spectra there are also relatively weak bands at 400, 440, and 465 cm ± ±1 as well as the 375 cm ± ±1 local band, all strongly correlated with the 600 cm ± ±1 broad band.…”
mentioning
confidence: 83%
“…It appears in proton-implanted Si : H samples following subsequent anneals at 300 to 500 C when two related levels at E c ± ± 0.06 eV and E c ± ± 0.1 eV are observed [2]. It was shown that the defect is a double donor with a ground spin-singlet state and that its concentration can exceed 10 16 cm ± ±3 and may be reversibly changed by quenching from 70 to 300 C to room temperature in water [3,4].…”
Section: Introduction a Hydrogen-intrinsic Defect-related Shallow Domentioning
confidence: 94%
See 1 more Smart Citation
“…One of the most interesting properties of implanted hydrogen is that its interaction with radiation--induced and native defects during heat treatment leads to the formation of high concentrations (up to 10 17 cm −3 ) of shallow hydrogen-related donors (H-donors) [2][3][4]. It is also important to note that H-donors do not contain oxygen atoms in our case [5].…”
Section: Introductionmentioning
confidence: 91%
“…It is also important to note that H-donors do not contain oxygen atoms in our case [5]. Most of the donor formation investigations were made for ≈ 100 µm thick floating zone grown Si layers produced using multi-energy H + ion implantation [3,4]. However, it was shown previously [6] that significant features in H-donors formation were observed in the submicron layers with high density of the introduced hydrogen.…”
Section: Introductionmentioning
confidence: 97%